A Nurse-Led Low-Cost Intervention Effectively Traces Prevalence of Catheter Associated Urinary Tract Infections at a Low-Resourced Regional Referral Hospital in Western Uganda: A Case for Policy Change - Etyang, Charles; Nambozi, Grace; Brennaman, Laura (Policy, Politics, & Nursing Practice, 2020)
Catheter associated urinary tract infection (CAUTI) is the most common hospital-acquired infection worldwide. Low- and middle-income countries (LMICs) with limited resources for health care have not allocated resources to adequately monitor or prevent CAUTIs. The infection is associated with several adverse clinical outcomes, including antibiotic resistance, septicemia, and prolonged hospital stays, that burden the already resource-constrained health systems in LMICs with increased morbidity, health care costs, and deaths. Owing to the lack of resource allocation, little is known about the prevalence of CAUTI in the government-owned and operated hospitals in LIMCs. The purpose of this research was to test a method of CAUTI prevalence surveillance suitable to the resource-constrained health system in a LMIC and to determine the prevalence of CAUTI among hospitalized patients at the study site. In an intermittent 4-week data collection plan, the sample of 68 catheterized adult participants was evaluated for the presence of CAUTI using the three-pronged screening criteria of American Urological Society. CAUTI prevalence in the sample was 17.6%. The high prevalence of CAUTI in this sample represents a substantial risk of consequences to hospitalized patients and to the resource-constrained health system in this LMIC. This first report of CAUTI surveillance using readily available and affordable tools provides evidence to health ministry policymakers of the need for and value of monitoring and prevention programs for hospital-acquired infections in LMICs.We recommend LMIC health policymakers to establish infection prevention teams in hospitals and provide resources to continue surveillance and prevention of CAUTI and other hospital-acquired infections.
Keywords: Hospital-acquired infection; Catheter-related infections; Resource allocation; Prevalence, prevalence study; Outcome assessments(Health care); Sub-Saharan Africa; Less developed countries